Penanganan Surat Menyurat Berbasis Elektronik di PT Bhanda Ghara Reksa (Persero) - Hartanti, Puput; Selfiana, Selfiana; Rahmawati, Siti (Jurnal Administrasi dan Kesekretarisan, 2021)
Abstract The use of written communication in the form of letters is an important medium in a company. The information contained in a letter is very valuable when the message is sent immediately. Competition between companies is very tight, completion of work with limited deadlines, requiring that any information can be sent and received immediately. Electronic-based mail handling is an option for companies. The purpose of this study was to determine the handling of incoming and outgoing mail in BUMN warehousing service companies. Qualitative methods with in-depth observation and interviews were conducted to obtain primary data. Secondary data were obtained from the company's electronic official correspondence application guide. The results showed that there were differences in procedures for handling incoming and outgoing mail. Keywords: electronic mail, incoming mail, outgoing mail. Abstrak Penggunaan komunikasi tertulis dalam bentuk surat menjadi media penting di sebuah perusahaan. Informasi yang tercantum di dalam sebuah surat sangat bernilai ketika pesan tersebut terkirim segera. Persaingan antar perusahaan yang sangat ketat, penyelesaian pekerjaan dengan tengat waktu yang terbatas, mengharuskan setiap informasi dapat di kirim dan diterima dengan segera. Penanganan surat berbasis elekronik menjadi pilihan bagi perusahaan. Tujuan penelitian ini untuk mengetahui penanganan surat masuk dan surat keluar di perusahaan jasa pergudangan milik BUMN. Metode kualitatif dengan observasi dan wawancara mendalam dilakukan untuk memperoleh data primer. Data sekunder diperoleh dari panduan aplikasi surat menyurat kedinasan secara elektronik milik perusahaan. Hasil penelitian menunjukkan ada perbedaan prosedur dalam menangani surat masuk dan surat keluar. Kata Kunci : surat elektronik,surat masuk, surat keluar